Application of Think Pair Share (TPS) Cooperative Learning Model Assisted by Ludo Media in History Learning Class XI Social Science at Senior High School - Ridha Riana*; Husaini Husaini (Universitas Syiah Kuala, 2022)
This study aims to determine how the application of the TPS learning model assisted by ludo media history learning, the obstacles faced by teachers and the responses of class XI IPS 1 student at SMA Negeri 6 Banda Aceh in applying the TPS learning model assisted by ludo media in history learning. This study uses a qualitative approach with descriptive research type, while the technique used was a purposve sampling technique. The data collection in this study was carried out by interview, observations, questionnaires and documentation. Based on the results of the study, it is knows that (1) The application of the TPS learning model assisted by ludo media in history learning for Class XI IPS 1 SMA Negeri 6 Banda Aceh is included in good criteria. (2) Obstacles faced by teachers in applying the TPS learning model assisted by ludo media in history learning, namely from the aspect of time, student and the Covid-19 national disaster. (3) Student responses to the TPS learning model assisted by ludo media were enthusiastic and enthusiastic even though they had never experienced it before. Learn to use the TPS learning model assisted by ludo media. There are also some who have difficulty in understanding the learning material. It is proven by the percentage of student responses on the questionnaire sheet which shows an average value of 76,5% which is in good criteria.